WHAT IS TRANSLATION STUDIES FOR? - Bismoko, J. Bismoko (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
What is translation studies for? Such a question, though currently relevant, may still become initially provoking, especially to established translation students. Why ask such a question? Indeed, it is a matter of choice to ask or not to ask it, nevertheless, in this paper I choose to offer an answer to this question. Essentially asking this question is only a logical consequence of the postmodern culture, to emphasize that a disciplined inquiry is to serve the student, and not the other way round. I will do it system wise, i.e. both systematically and systemically. The system treatment is to allow not a peace-meal but more holistic coverage of the subject matter, from its metaphysics to its operation. I am hoping the discussion will help translation students think big and act small in developing a more authentic project of translation studies.